Optimization and Matching Scheme of Public Management Resources for Industry 4.0 and Smart City - Jinglin Fan; Lei Shi (Complexity)
With the development of Big Data, Industry 4.0, and other technologies, the concept of smart city has become a new goal, new concept, and new practice of many urban developments. It provides a method to solve the problem that public management cannot optimize resources in China’s urban development and puts forward a supporting scheme more in line with the optimization of public management resources. Effective use of relevant supporting schemes can improve urban public management capacity, optimize resources, and promote the city to embark on the road of scientific development. This paper starts with the multiobjective optimization algorithm to optimize the matching of public resources and realize the effective utilization of public management resources. Using particle swarm optimization algorithm, the optimal allocation management of 8 kinds of resources in this paper is carried out, and the optimization analysis is carried out from the performance indexes, such as resource allocation time and configuration complexity. Finally, the weights of the eight resources in importance, complexity, and resource demand are 0.4, 0.4, and 0.2, respectively. The proposed method realizes the classification of resources and the optimal matching of resources.